Pericardial hyperechogenicity and “comets” in patients with acute pericarditis but no pericardial effusion: a comparison study with age-matched healthy controls. - Sartorio, Daniele; Siniscalchi, Carmine; Reverberi, Claudio; Gaibazzi, Nicola (Acta Biomedica Atenei Parmensis, 2016)
Background and aim: According to the published data and guidelines the diagnosis of pericarditis is mainly clinical; if we exclude patients with pericardial effusion, no single study has been able to relate specific echocardiographic findings to acute pericarditis. We hypothesized that pericardial hyperechogenicity and a defined finding that we named “pericardial comets”, in analogy to lung comets, may be associated with acute pericarditis.Methods: We retrospectively analysed the echocardiograms of patients aged 50 y/o) to detect a potential association of pericardial hyperechogenicity and/or pericardial comets with acute pericarditis.Results: Comparison between the pericarditis and the control groups did not evidence significant differences regarding the prevalence of hyperechogenicity and pericardial comets when comparing patients with pericarditis and age-matched controls (younger than 50 years); the group of elderly healthy controls (>50 y/o) showed significantly lower prevalence of pericardial hyperechogenicity (p